Data Transmission Parameters of Reservoir Water PT. Meteor Perkasa Uses Long-Distance Communication - Natasya, Audrey Nanda; Marpaung, Jannus; Putra, Leonardus Sandy Ade (Faculty of Engineering, Universitas Tanjungpura, 2024)
The company engaged in the production of bottled drinking water (AMDK) is PT Meteor, the product produced is the